Accumulation of tissue factor in endothelial cells induces cell apoptosis, mediated through p38 and p53 activation - ElKeeb, Azza M; Collier, Mary E.W.; Maraveyas, Anthony; Ettelaie, Camille (Thrombosis and Haemostasis, 2015)
We previously reported that high levels of tissue factor (TF) can induce cellular apoptosis in endothelial cells. In this study, TF-mediated mechanisms of induction of apoptosis were explored. Endothelial cells were transfected to express wild-type TF. Additionally, cells were transfected to express Asp253-substituted, or Ala253-substitued TF to enhance or prevent TF release, respectively. Alternatively, cells were pre-incubated with TF-rich and TF-poor microvesicles. Cell proliferation, apoptosis and the expression of cyclin D1, p53, bax and p21 were measured following activation of cells with PAR2-agonist peptide. Greatest levels of cell proliferation and cyclin D1 expression were observed in cells expressing wild-type or Asp253-substituted TF. In contrast, increased cellular apoptosis was observed in cells expressing Ala253-substituted TF, or cells pre-incubated with TF-rich microvesicles. The level of p53 protein, p53-phosphorylation at ser33, p53 nuclear localisation and transcriptional activity, but not p53 mRNA, were increased in cells expressing wild-type and Ala253-substituted TF, or in cells pre-incubated with TF-rich microvesicles. However, the expression of bax and p21 mRNA, and Bax protein were only increased in cells pre-incubated with TF-rich microvesicle and in cells expressing Ala253-substituted TF. Inhibition of the transcriptional activity of p53 using pifithrin-α suppressed the expression of Bax. Finally, siRNA- mediated suppression of p38α, or inhibition using SB202190 significantly reduced the p53 protein levels, p53 nuclear localisation and transcriptional activity, suppressed Bax expression and prevented cellular apoptosis. In conclusion, accumulation of TF within endothelial cells, or sequestered from the surrounding can induce cellular apoptosis through mechanisms mediated by p38, and involves the stabilisation of p53.
Keywords: Tissue factor; serine-phosphorylation; p38-MAP kinase; p53 activation; apoptosis